Chemotherapy induced cardiotoxicity: on the way to personalized risk stratification based on genetic variants. (11th May 2022) - Boen, H; Loeys, B; Van Laer, L; Heidbuchel, H; Alaerts, M; Franssen, C; Van Craenenbroeck, EM
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): 1.Flanders Research Foundation- FWO (doctoral research grant) 2.UZA Foundation-Wolvenbos Grant 2019 Background: Anthracycline chemotherapy is a cornerstone in the treatment of several malignancies. However, it causes substantial toxicity, of which cardiotoxicity is the most frequent and most severe (1). Ideally, patients at risk for cardiotoxicity are identified prior to treatment, however, traditional patient- and treatment-related factors fail to fully predict the individual risk at the moment. Improved risk stratification for ANT-induced cardiotoxicity could possibly be reached by taking genetic risk factors into account. Purpose: We assessed the prevalence of variants in genes encoding for cardiac proteins in the development of anthracycline-induced cardiotoxicity. Methods: Patients presenting with early (< 1y) or late (> 1y) anthracycline-induced cardiotoxicity between 1995 and 2020 were included. Cardiotoxicity was defined as a decline in left ventricular ejection fraction (LVEF) to <50% and a ≥10% reduction from baseline by echocardiography. Genetic analysis was offered using a haloplex gene panel composed of 59 known cardiomyopathy-related genes. Variants were classified according to ACMG guidelines(2). Both variants of unknown significance (VUS, class 3) and likely pathogenic/pathogenic variants (class 4 and 5) were taken into account. Frequency of genetic variants was compared to a matched positive control cohort of patients with dilated cardiomyopathy (DCM). Results: Forty-two patients that had developed cardiotoxicity (mean age at time of diagnosis 54yrs) fulfilled the inclusion criteria and agreed to genetic testing. The majority of patients had been treated for lymphoma (52.4%) or breast cancer (38.1%). Total equivalent dose of anthracyclines averaged 285.5 mg/m² doxorubicin. Patients showed an average reduction in LVEF of 27.1% (+- 10.1). In 18 patients (42.9 %), a variant could be identified; 15 patients carried a variant of unknown significance (VUS) and 3 carried a likely pathogenic variant. In total 29 variants different variants were identified in 18 distinct individuals. Genetic yield was independent of anthracycline-dose and the presence of other cardiovascular risk factors. The genetic yield in cardiotoxicity patients did not differ significantly from this in DCM-controls (18/42 VUS, 5/42 (likely) pathogenic variants, p = 0.19). After initiation of standard heart failure therapy, 6 (33.3%) of variant carriers showed incomplete recovery of cardiac function, compared to only 3 (12.5%) of patients who did not carry a variant (p=0.103). Conclusion: Prevalence of genetic variants in anthracycline-induced cardiotoxicity is similar to that in isolated dilated cardiomyopathy. This finding supports a second-hit mechanism in which anthracycline chemotherapy, uncovers a genetically determined cardiomyopathy. As such, genetic variants in cardiomyopathy genes could improve individualized risk stratification prior to anthracycline chemotherapy and can assist in personalized prevention of this feared side effect of chemotherapy.